2001
DOI: 10.1128/aac.45.10.2710-2715.2001
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Profile and Tolerability of Indinavir-Ritonavir Combinations in Healthy Volunteers

Abstract: This was a randomized, double-blind, placebo-controlled parallel study in human immunodeficiency virus type 1 (HIV-1)-uninfected healthy subjects to investigate the pharmacokinetic interaction between indinavir (IDV) and ritonavir (RTV). Subjects were allocated to treatment groups of IDV given with RTV in the following milligram doses twice daily: 800 mg of IDV-100 mg of RTV (800-100 mg), 800-200, 800-400, and 400-400 mg, placebo of IDV with RTV doses of 100, 200, and 400 mg, and placebo of both IDV and RTV. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
75
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 12 publications
(4 reference statements)
6
75
2
Order By: Relevance
“…2 h. Ritonavir more dramatically altered the shape of the indinavir concentration in plasma curve, greatly increasing C min but not affecting C max or time to C max . The effect of ritonavir on the indinavir concentration profiles in plasma is generally consistent with a recent study that showed that low-dose ritonavir increased the geometric mean indinavir C max by Ͻ2-fold, the AUC 0-24 by Ͻ3-fold, and the C trough by Ͼ10-fold in HIV-negative volunteers (25). Since C min may best predict antiviral effect for HIV-1 protease inhibitors, concomitant ritonavir should enhance indinavir's antiviral effect in both peripheral and central nervous system compartments.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…2 h. Ritonavir more dramatically altered the shape of the indinavir concentration in plasma curve, greatly increasing C min but not affecting C max or time to C max . The effect of ritonavir on the indinavir concentration profiles in plasma is generally consistent with a recent study that showed that low-dose ritonavir increased the geometric mean indinavir C max by Ͻ2-fold, the AUC 0-24 by Ͻ3-fold, and the C trough by Ͼ10-fold in HIV-negative volunteers (25). Since C min may best predict antiviral effect for HIV-1 protease inhibitors, concomitant ritonavir should enhance indinavir's antiviral effect in both peripheral and central nervous system compartments.…”
Section: Discussionsupporting
confidence: 89%
“…It is more commonly used as a "pharmacokinetic enhancer." Ritonavir increases plasma AUCs, half-lives, and trough concentrations of indinavir and other protease inhibitors by inhibiting the 3A4 isoform of cytochrome P450 (13,20,25) and overcomes the negative effect of food on indinavir bioavailability. Comparing detailed pharmacokinetic data from our previous study (17) with data from the present study allowed the effect of ritonavir on indinavir disposition into CSF to be thoroughly characterized.…”
Section: Discussionmentioning
confidence: 99%
“…All parameters included log-normal interindividual error terms. The absorption rate constant (K a ), V/F, and the transfer rate constants between the central and peripheral compartments (K 23 and K 32 ) were modeled separately for days 1 and 14. It cannot be determined if these effects are dependent on time or on the administration of ritonavir.…”
Section: Methodsmentioning
confidence: 99%
“…All HIV PIs are substrates and inhibitors of CYP3A4, but the HIV PI ritonavir is the most potent inhibitor of CYP3A4 (Woolley et al, 37th ICAAC). Previous studies have indicated significant increases in drug exposure from coadministration of ritonavir with indinavir, saquinavir, and nelfinavir (12,13,18,19,22,23,30; D. Burger, P. Hugen, H. Hofstede, P. Koopmans, M. Stek, Jr., P. Reiss, and J. Lange, Abstr. 37th Intersci.…”
mentioning
confidence: 99%
“…15,16 However, this is the first study to demonstrate that coadministration of ritonavir with indinavir may offset the pH-dependent decrease in indinavir exposure observed when coadministered in single doses with omeprazole. An increase in indinavir's AUC 0-24 after coadministration of ritonavir is well-known.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 85%